Long-distance truck drivers and the increasing risk of COVID-19 spread in Uganda - Bajunirwe, Francis; Izudi, Jonathan; Asiimwe, Stephen (International Journal of Infectious Diseases, 2020)
Objective: To examine the patterns of COVID-19 transmission in Uganda. Methods: We reviewed ten weeks of press releases from the Uganda Ministry of Health from the day when the first case was announced, March 22, through May 29, 2020. We obtained the press releases from the MoH website and the Twitter handle (@Min of Health UG). Data include the number of persons tested and the categories were classified as international arrivals, community members, and long-distance truck drivers. Results: The first cases were international arrivals from Asia and Europe, and after that, community cases emerged. However, in the middle of April 2020, COVID-19 cases were detected among long-distance truck drivers. By May 29, 2020, 89, 224 persons had been tested; overall, 442 tested positive. Of those that tested positive, the majority, or 317 (71.8%) were truck drivers, 75 (16.9%) were community cases, and 50 (11.3%) were international arrivals. The majority of community cases have been linked to contact with truck drivers. Conclusions: Truck drivers were the most frequently diagnosed category, and have become a core group for COVID-19 in Uganda. They have generated significant local transmission, which now threatens a full-blown epidemic unless strict controls are put in place.
Keywords: Truck drivers; COVID-19; Uganda; Transmission